Efficient management of the application of paclobutrazol for the production and quality of 'Tommy Atkins' mango (Research, Society and Development, 2020)
The application of paclobutrazol (PBZ) by irrigation system to induce the flowering of mango may be an economically and environmentally more efficient practice. The objective of this work is to determine the most efficient dose of PBZ to be applied by irrigation system to manage the production and quality of fruits of the mango cultivar ‘Tommy Atkins’ in the middle region of the São Francisco Valley. The experimental design was randomized blocks with five paclobutrazol doses applied by irrigation system (0.5, 1.0, 1.5, 2.0 and 2.5 g a.i.-1, linear canopy) and an additional treatment (control) with the application of a dose using the conventional form (2.0 g a.i.-1 linear canopy applied manually by haul), and four replications. The variables analyzed were number of panicles, panicle length, number of fruits per plant, average fruit weight, production per plant, economic viability, and qualitative characteristics of fruits. The application of paclobutrazol by irrigation system is more efficient than the conventional application, in which the dose 1.4 g a.i.-1 linear canopy provided a greater number of fruits and a greater production per plant. The highest content of total soluble solids in fruits was obtained at the dose 1.3 g a.i.-1 linear canopy, and acidity decreased as the applied dose of PBZ increased. Regarding the economic analysis, the results show that the application of PBZ by irrigation system increases the revenue by R$ 5,328.00 per hectare in comparison with the conventional application.